At the Nexus of Antibiotics and Metals: The Impact of Cu and Zn on Antibiotic Activity and Resistance. Issue 10 (October 2017) - Poole, Keith
Abstract : Environmental influences on antibiotic activity and resistance can wreak havoc with in vivo antibiotic efficacy and, ultimately, antimicrobial chemotherapy. In nature, bacteria encounter a variety of metal ions, particularly copper (Cu) and zinc (Zn), as contaminants in soil and water, as feed additives in agriculture, as clinically-used antimicrobials, and as components of human antibacterial responses. Importantly, there is a growing body of evidence for Cu/Zn driving antibiotic resistance development in metal-exposed bacteria, owing to metal selection of genetic elements harbouring both metal and antibiotic resistance genes, and metal recruitment of antibiotic resistance mechanisms. Many classes of antibiotics also form complexes with metal cations, including Cu and Zn, and this can hinder (or enhance) antibiotic activity. This review highlights the ways in which Cu/Zn influence antibiotic resistance development and antibiotic activity, and in so doing impact in vivo antibiotic efficacy. Trends: The environment can influence both antibiotic activity and bacterial susceptibility to antibiotics, and understanding the impact of environmental factors is key to predicting in vivo antibiotic efficacy. Metal cations are common environmental stressors that perturb bacteria, activating metal-protective stress responses and growth states that also protect against and provide resistance to antibiotics. Metal (Cu and Zn) and antibiotic resistance genes co-occur in animal isolates of multidrug-resistant Salmonella and methicillin-resistant Staphylococcus aureus (MRSA). This reflects the demonstrated genetic linkage of the resistance genes and highlights the potential for metals to drive antibiotic resistance development in human pathogens. Cu and Zn are antimicrobials in their own right, and their use in combination with or complexed to certain antibiotics can enhance antibiotic efficacy.